Prolonged hematological toxicity in patients receiving BCMA/CD19 CAR-T-cell therapy for relapsed or refractory multiple myeloma - Li, Hujun; Zhao, Lina; Sun, Zengtian; Yao, Yue; Li, Li; Wang, Jiaojiao; Hua, Tian; Ji, Shengwei; Wang, Shiyuan; Cheng, Hai; Shi, Ming; Li, Zhenyu; et al. (Frontiers in Immunology, 2022)
Although chimeric antigen receptor T (CAR-T) cell therapy has been indicated to be effective in treating relapsed or refractory multiple myeloma (R/R MM), severe hematological toxicity (HT) remains an intractable issue. This study enrolled 54 patients with R/R MM following combined infusion of anti-CD19 and anti-BCMA CAR-T cells. The results showed that the rates of severe cytopenia were high, including severe neutropenia (28/54, 52%), severe anemia (15/54, 28%), and severe thrombocytopenia (18/54, 33%). Moreover, the incidence of prolonged HT (PHT) on Day 28 post-infusion was 52% (28/54), including 46% for severe neutropenia, 30% for severe anemia, and 31% for severe thrombocytopenia. Patients with PHT had a poorer median progression-free survival (PFS) and overall survival (OS) than patients without PHT (P=0.011; P=0.007). Furthermore, Cox regression analyses showed that PHT was an independent risk factor for PFS and OS. Univariate analyses showed that IFNγ (OR: 1.046; 95% CI: 1.002-1.093, P=0.042) and severe HT after lymphodepletion chemotherapy (OR: 0.082; 95% CI: 0.017-0.404; P=0.002) were independent risk factors for PHT. In conclusion, these results indicated that PHT was associated with poor outcomes following CAR-T-cell therapy in MM patients. Early detection and management of PHT would be beneficial for the prevention of life-threatening complications and improvement in the survival of patients after CAR-T-cell therapy. Clinical trial registration This trial was registered on 1 May 2017 at http://www.chictr.org.cn as ChiCTR-OIC-17011272.